Analysis of Starch Grains Produced in Select Taxa Encountered in Southwest Asia - Hart, Thomas C. (Ethnobiology Letters, 2014)
Starch grain analysis is a rapidly growing field of research in Southwest Asia and is beginning to be applied to many different time periods. However, much work still remains regarding which taxa produce starch grains that can be identified archaeologically. In this paper, I centralize what is known about starch production patterns within regional flora and analyze 64 previously unstudied taxa from 22 families. The results of this study demonstrate that descriptions of starch grains from Southwest Asian taxa are scattered between archaeological and plant and food science publications. Ten of the species examined in this study, most of whom are grasses, produced starch grains that can be identified at varying taxonomic levels.